2020
DOI: 10.1159/000506899
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of High Fructose Diet-Induced Insulin Resistance, Hyperuricemia, and Liver Oxidative Stress by Combined Use of Selective Agonists of PPAR-α and PPAR-γ in Rats

Abstract: Background: The use of high-fructose (Fr) corn sweeteners and sucrose in manufactured food has markedly increased recently. This excessive Fr intake has been proposed in the etiology of the metabolic syndrome, which shows an increasing prevalence throughout the world. Objective: In this study, we questioned whether fenofibrate (FF), a peroxisome proliferator-activated receptor (PPAR)-α agonist, and pioglitazone (PG), a PPAR-γ agonist, might be effective in ameliorating the metabolic syndrome in a rat model. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 50 publications
6
6
0
Order By: Relevance
“…In this study, administration of high fructose drinking water to the disease group increased their hepatic SOD activity and MDA concentrations but decreased their hepatic CAT activity, suggesting fructose‐induced hepatic oxidative stress. Similar reports on the induction of hepatic oxidative stress following administration of high fructose diets in rats were also given by Francini et al (2010) ; Prabhakar et al (2014) and Farag et al (2020), respectively.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In this study, administration of high fructose drinking water to the disease group increased their hepatic SOD activity and MDA concentrations but decreased their hepatic CAT activity, suggesting fructose‐induced hepatic oxidative stress. Similar reports on the induction of hepatic oxidative stress following administration of high fructose diets in rats were also given by Francini et al (2010) ; Prabhakar et al (2014) and Farag et al (2020), respectively.…”
Section: Discussionsupporting
confidence: 79%
“…Insulin resistance refers to the decreased ability of target tissues, such as liver, adipose, and muscle, to properly respond to normal or increased concentrations of insulin in circulation (Ferrier, 2014). Excess or regular intake of fructose contributes to insulin resistance development through fructose‐mediated induction of oxidative stress and inflammation (Farag et al, 2020; Horst & Serlie, 2017; Jaiswal et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most prominent pathological features of MS correlated with the diagnostic conditions of human MS is IR 50 . In the present study, HFHF administration resulted in IR, as characterized by the elevated HOMA-IR score.…”
Section: Discussionmentioning
confidence: 99%
“…The suppressing effect of TNF-α upon liver insulin action is achieved by interrupting insulin signaling via serine phosphorylation of insulin receptor proteins 50 , 51 . Accordingly, in the present study, the neutralization of TNF-α by ETA enhanced insulin sensitivity as indicated by the normalized HOMA-IR and significantly reduced fasting glucose and insulin serum levels compared with those in the HFHF group.…”
Section: Discussionmentioning
confidence: 99%